Speech Prosody 2016 2016
DOI: 10.21437/speechprosody.2016-130
|View full text |Cite
|
Sign up to set email alerts
|

Affirmative constituents in European Portuguese dialogues: Prosodic and pragmatic properties

Abstract: This paper investigates the correlation between the prosodic properties and pragmatic functions of affirmative constituents in adult-adult interactions in European Portuguese (CORAL corpus). 515 affirmative constituents produced in 460 answers, extracted from 11 dialogues between 12 speakers, were analyzed. Results show that: i) sim 'yes', ok and grunts are the most frequent affirmative constituents; ii) sim 'yes' is associated with all the communicative functions analyzed, agreement, auto positive and confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…While studying affirmative answers in European Portuguese, [3], in the same corpus used in this study, found evidences of pitch concord effects in context-answer pairs with different pragmatic functions. The authors found correlations regarding pitch height between the pairs instruct-agreement and propositional question (yes-no question) -confirm, although expressed in different degrees.…”
Section: Related Workmentioning
confidence: 52%
“…While studying affirmative answers in European Portuguese, [3], in the same corpus used in this study, found evidences of pitch concord effects in context-answer pairs with different pragmatic functions. The authors found correlations regarding pitch height between the pairs instruct-agreement and propositional question (yes-no question) -confirm, although expressed in different degrees.…”
Section: Related Workmentioning
confidence: 52%
“…In EP, only two studies have addressed adaptation between speakers, [18], and [19], both using a subset of the same maptask corpus used in this study. [18] found evidences of prosodic correlations (pitch concord effects) between Yes/No-questions and affirmative answers; and [19] found global entrainment expressed in different degrees, since speakers did not entrained with the same partners and in the same features. Results showed that, despite the role speakers were playing (giver or follower), they tended to display more sensitivity to some partners, which may reveal a stronger partner effect than a role effect.…”
Section: State-of-the-artmentioning
confidence: 99%